Determining optimum air-void spacing requirement for a given concrete mixture design using poromechanics. Issue Volume 19:Issued 7(2018) (3rd July 2018) - Rahman, Syeda; Grasley, Zachary
Abstract: The frost resistance of concrete is a function of the concrete constituent properties, entrained air-void system parameters and environmental exposure history. However, only a single maximum value for the void spacing factor is specified for all types of concrete by code writing bodies for successful protection against freezing damage. The advent and utilisation of new materials over the recent years warrant reevaluation of the validity of this single pass/fail criteria established more than 50 years ago. Here, a poromechanical model, capable of incorporating concrete constituent properties, environmental exposure and air-void spacing factor, has been used to determine the role of various concrete constituents and air-void system on the damage propensity of concrete exposed to freezing temperatures. It is found that a maximum threshold of acceptance, for instance a 0.2 mm spacing factor, may not be adequate for all concrete mixture designs subject to various cooling conditions. The model also suggests that concrete with low-porosity, low-permeability mortar matrix, a characteristic property of mortar containing supplementary cementitious materials and/or low water to cement ratio, can perform satisfactorily under freezing temperatures even with a spacing factor greater than the recommended value. If utilised for design, this model will give more freedom to practitioners in ensuring concrete durability by controlling multiple factors including the concrete mixture components and proportions rather than just satisfying a single pass/fail criterion for void spacing factor for all concrete mixtures.